A Dynamic Bankruptcy Forecasting Model for Ensuring Sustainability in the Islamic Banking: Following the COVID-19 Pandemic - Maran MARIMUTHU; Mehreen MEHREENand Amin JAN (Communications of International Proceedings, 2021)
To achieve high sustainability in Islamic banking following the COVID-19 pandemic, this research aims to develop a new dynamic bankruptcy forecasting model for Islamic banking. The process involves combining variables from three important business aspects that can trigger bankruptcy. The three aspects include financial indicators, corporate sustainability (in line with Sustainable Development Goals SDGs), and the Islamic Corporate Governance (ICG). The compelling force behind the development of the model is based on the dilemma that a bankruptcy forecasting model which is grounded on Shariah principles is still missing. The proposed bankruptcy evolution model will first identify those financial indicators that are relevant to predicting bankruptcy in the case of Islamic banking. Secondly, it will (identify and integrate) sustainability variables to the envisioned bankruptcy forecasting model which as a twofold effect will reduce bankruptcy chances and will ensure compliance of Islamic banks with SDGs. Thirdly the inclusion of Islamic Corporate Governance variables to the deemed bankruptcy forecasting model will modernize the concept of corporate governance beyond the traditional monitoring process towards providing bankruptcy surveillance as well. A secondary data related to the three strands of the proposed model will be collected from the published sources including (financial reports, annual reports and sustainability reports) for the sample of the study i.e., top five market-leading Islamic banking countries based on the size of their total assets. The sampled countries are Malaysia, Saudi Arabia, Iran, Kuwait and UAE. The proposed model may have important policy-based implications for Islamic banking for achieving higher business sustainability. It may also provide policy-based guidelines to the practitioners of Islamic banking for compliance with SDGs. Compliance with SDGs through Islamic banking sustainability instruments at this point of time will mitigate the distressing impact of COVID-19 on people, profit and planet.
Keywords: Bankruptcy forecasting; sustainable business practices; corporate governance; Islamic Banking; SDGs; COVID-19